Urgensi Pendidikan Keluarga Sakinah dalam Mengurangi Dispensasi Pernikahan Anak: Studi Putusan Pengadilan Agama Temanggung Nomor : 103/Pdt.P/2025/PA.Tmg. - Badik Atus Solikhah; Hamidulloh Ibda; Joni; Muhammad Syakur; Sumarjoko; Baehaqi (At Turots: Jurnal Pendidikan Islam, 2025)
The phenomenon of child marriage dispensation in Indonesia remains a serious issue with implications for child protection, education, reproductive health, and social welfare. This study examines the urgency of sakinah family education in preventing and reducing the practice of marriage dispensation, with a particular focus on the Temanggung Religious Court Decision Number : 103/Pdt.P/2025/PA.Tmg. The research employs a normative juridical method with a case study approach, in which the primary data consists of the official copy of the court ruling, supported by relevant regulations such as Law Number 16 of 2019, the Compilation of Islamic Law, and Supreme Court Regulation Number 5 of 2019. The findings reveal that the judge granted the dispensation on the grounds of an urgent circumstance, namely the out-of-wedlock pregnancy of the prospective bride. However, this decision presents a dilemma as it conflicts with the principle of child protection. The article emphasizes that sakinah family education which highlights the strengthening of religious values, morality, and social responsibility within the family serves as an effective preventive instrument to reduce the prevalence of child marriage dispensation.